Textures of Struggle The Emergence of Resistance among Garment Workers in Thailand - Pangsapa, Piya (Cornell University Press, 2011)
Based on intensive ethnographic fieldwork in Thailand, Textures of Struggle focuses on the experiences of Thai women who are employed at textile factories and examines how the all-encompassing nature of wage work speaks to issues of worker accommodation and resistance within various factory settings. Why are some women less tolerant of their working conditions than others? How is it that women who have similar levels of education, come from the same socioeconomic background, and enter the same occupation, nevertheless emerge with different experiences and reactions to their wage employment?Women in the Thai apparel industry, Piya Pangsapa finds, have very different experiences of labor "militancy" and "non-militancy." Through interviews with women at two kinds of factories-one linked to the global economy through local capital investment and another through transnational capital-Pangsapa examines issues of worker consciousness with a focus on the process by which women become activists.She explores the different degrees of control and coercion employed by factory managers and shows how women were able to overcome conditions of adversity by relying on the close personal ties they developed with each other. Textures of Struggle reveals what it is like for women to feel powerlessness and passivity in Thai sweatshops but also shows how they are equally able to resist and rebel